Mengurangi Downtime Mesin Conveyor di Asembly Line Bodi Kendaraan dengan Metode Quality Control Circle - Rinaldi, Rinaldi; Indratama, Aria; Prasetya, Raynaldi Yudha; Koerniawan, Yani (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The operation of conveyor machines as one of the manufacturing production tools inevitably carries the risk of line stop issues, which negatively impact efficiency due to machine or robot errors and halts. This study discusses improvements to reduce downtime of conveyor machines widely used at PT XYS by applying the Quality Control Circle (QCC) method. The results indicate that machine errors were primarily caused by the controller's temperature exceeding standard limits, leading to damage in the output power voltage due to instability. As a countermeasure, a cooling fan was installed to lower the controller temperature. This effort successfully reduced the average monthly downtime from 1,468 minutes to 476 minutes. The improvement was further supported by updates to the Standard Operating Procedure (SOP) and the implementation of a preventive maintenance checksheet.